2018
DOI: 10.3389/fpsyt.2018.00348
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Predictors of Postpartum Posttraumatic Stress Disorder in Women With a Traumatic Childbirth Experience

Abstract: Objective: To analyze the predictive value of antepartum vulnerability factors, such as social support, coping, history of psychiatric disease, and fear of childbirth, and intrapartum events on the development of symptoms of postpartum posttraumatic stress disorder (PP-PTSD) in women with a traumatic childbirth experience.Materials and methods: Women with at least one self-reported traumatic childbirth experience in or after 2005 were invited to participate through various social media platforms in March 2016.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 25 publications
3
68
1
1
Order By: Relevance
“…Additionally, Ryding et al in aninvestigation for PTSD reaction among women with EMCS, showedthat 1/3 of the study population sufferedfrom serious PTSD reactions [21]. On the contrary, the study by Lopez et al didnot find an association between the kind of CS and PTSD [19].Additionally, the paper published by van Heumen et al defends thatpsychosocial characteristics arestronger predictors than the kind of delivery [8]. However, this study found that 13.1% of the study population met the DSM-V criteria for PTSD (31.7% after EMCS and 1% after ELCS), while 8.1% of women were suffering from PTSD Profile according to the DSM -V (14.3% after EMCS and 4.1% after ELCS) ( Table 3).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Additionally, Ryding et al in aninvestigation for PTSD reaction among women with EMCS, showedthat 1/3 of the study population sufferedfrom serious PTSD reactions [21]. On the contrary, the study by Lopez et al didnot find an association between the kind of CS and PTSD [19].Additionally, the paper published by van Heumen et al defends thatpsychosocial characteristics arestronger predictors than the kind of delivery [8]. However, this study found that 13.1% of the study population met the DSM-V criteria for PTSD (31.7% after EMCS and 1% after ELCS), while 8.1% of women were suffering from PTSD Profile according to the DSM -V (14.3% after EMCS and 4.1% after ELCS) ( Table 3).…”
Section: Discussionmentioning
confidence: 97%
“…This prospective study is the firstto investigate the development of PTSD and PTSD Profile in two groups of high-risk postpartum women (EMCS and ELCS). Furthermore, it is one of the few studieswhere they used all the diagnostic criteria (A, B, C, D, E) for PTSD postpartum, according to the DSM-V( Table 3) [8] and this increases the sensitivity of the measure, compared with similar surveys in the past.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations